The Effect on Long Term Survivorship of Surgeon Preference for Posterior Stabilized or Minimally Stabilized Total Knee Replacement: An Analysis of 63416 Cases from the AOANJRR. Issue 5 (31st May 2017) - Vertullo, Christopher; Lewis, Peter; Lorimer, Michelle; Graves, Stephen
Introduction & Aims: Controversy still exists as to the optimum management of the PCL in TKR, with registry data suggesting Posterior Stabilised TKR have a higher Cumulative Percent Revision (CPR) compared to Minimally Stabilised TKR. Proponents of PS TKR suggest this difference is due to selection bias as result of preferential use of PS TKR in complex or more severe cases. To remove this selection bias, we aimed to compare CPR based on surgeon TKR stability preference to treat with PS or MS TKR rather than actual prosthesis type received. Method: Observational series. An analysis of AOANJRR data from 1999 – 2014 was utilized to identify two cohorts of high volume surgeons who preferred to use routinely either MS or PS TKR. Only fixed tibial inserts and patellar resurfacing TKR were included. A MS preferring surgeon used MS TKR at least 90% of the time and a PS preferring surgeon used PS TKR at least 90% of the time. Consequently, each patient cohort included both PS and MS TKR in differing proportions. Results: Procedures undertaken by PS preferring surgeons had a significantly higher risk of revision (CPR (Hazard Ratio = 1.45 (95% CI 1.30, 1.63), p< 0.001). There was a higher rate of revision for loosening and infection in the PS group. Of the 39 941 TKR with cemented fixation of both femur and tibia, the PS preferring surgeons had a higher CPR than the MS preferring cohort (HR = 1.55 (1.33, 1.80), p< 0.001). Regardless of whether the polyethylene was crosslinked or non-crosslinked, the MS preferring surgeons had a lower CPR compared to the PS preferring surgeons. Conclusions: In this analysis, procedures undertaken by surgeons who mainly preferred to use PS TKR had a higher rate of revision than those that mainly used MS TKR. This finding was irrespective of patient age and was also evident when fixation and the type of polyethylene used was taken into account.